2011
DOI: 10.1007/s00417-011-1895-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the biocompatibility of two new heavy intraocular dyes for vitreoretinal surgery with an isolated perfused vertebrate retina organ culture model and a retinal ganglion cell line

Abstract: ILM Blue and MBB Dual seem to be safe for clinical use for a staining period of up to 120 seconds, probably even up to 320 seconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…2), in agreement with the well-documented neuroprotective effects of PEG [64]. Apart from the study on ARPE cells, electrophysiological evaluation did not reveal any detrimental effects of MembraneBlue-Dual on retinal ganglion cells in vitro, with application times up to after 5 min [65]. Combined, these results indicate MembraneBlue-Dual to be biocompatible and safe for clinical use.…”
Section: Figsupporting
confidence: 79%
“…2), in agreement with the well-documented neuroprotective effects of PEG [64]. Apart from the study on ARPE cells, electrophysiological evaluation did not reveal any detrimental effects of MembraneBlue-Dual on retinal ganglion cells in vitro, with application times up to after 5 min [65]. Combined, these results indicate MembraneBlue-Dual to be biocompatible and safe for clinical use.…”
Section: Figsupporting
confidence: 79%
“…MBB Dual showed also in this study significant effects [45]. Therefore, MBB Dual should also be considered with the background of our results of TB alone [19].…”
mentioning
confidence: 59%
“…Adding heavy water to increase the density of the BBG solution facilitates sedimentation on the retina. The alternatives that exist are adding glucose or PEG 3350 to create a heavier dye [44,45]. The data from our model indicate that epiretinally applied BBG 0.4 ml (0.25 mg/ml) combined with 4.4% glucose has no toxic effects on the retinal function, and seems to be safe for clinical use.…”
mentioning
confidence: 86%
“…Several studies showed that ILM peeling was associated with a lower rate of recurrence, and ILM peeling was considered essential to remove the scaffold for further cell proliferation [5,6,13]. The intraoperative use of vital dyes for visualization of the ERM and ILM has been introduced to allow a complete and safe removal of the membranes during the surgery procedure [15][16][17][18][19][20][21][22]32]. The purpose of the present study was to report on the combined use of TB and BBG for staining ERM and ILM during vitrectomy and to describe the histopathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the 0.15% TB, 0.025% BBG, and 4.00% polyethylene glycol (PEG) combination (MembraneBlue-Dual TM , DORC International, Zuidland, the Netherlands) has been introduced for staining both the ILM and ERM [31,32]. This heavy vital dye is commercially available in Europe.…”
Section: Introductionmentioning
confidence: 99%